Rostro-caudal networks for sound processing in the primate brain - Scott, Sophie K.; Jasmin, Kyle (Frontiers in Neuroscience, 2022)
Auditory processing in primates is neuroanatomically and functionally bifurcated. There are several models of speech and auditory processing in the human brain built around this principle (Alain et al., 2001; Hickok & Poeppel, 2004; Rauschecker & Scott, 2009; Jasmin et al., 2019), which originated in work on non-human primates (NHP).